Oral Manifestations in Diabetes Mellitus and Management Considerations: A Review : Life Sciences- Oral Medicine - R. Sonar, Dr. Prasanna; S. Panchbhai, Dr. Aarati; Mishra, Dr. Sunil; B. Dangore, Dr. Suwarna (International Journal of Life Science and Pharma Research, 2023)
Diabetes mellitus is a chronic metabolic disorder defined as an increase in sugar levels in the bloodstream brought onby either insufficient insulin secretion, resistance to insulin's effects, or both. All age groups are affected by the chronic conditionknown as diabetes mellitus. It is among the world's major causes of mortality and morbidity. Xerostomia, dental caries,periodontal disease, gingivitis, candidiasis, other oral infections, burning mouth syndrome, taste dysfunction, oral mucosalalterations, delayed wound healing, and localized osteitis are common oral manifestations of diabetes mellitus. Majorcomplications impacting a patient's quality of life include oral complications in diabetic individuals. Long-term oral problems inthese patients’ harm blood glucose regulation, making oral complications care and prevention important. The dental professionalshould be familiar with DM's oral manifestations to identify this disease complication. This article not only discusses the oralmanifestations but also discusses management considerations in diabetic patients which will help future dental professionals indental practice. This article aims to spread knowledge and awareness about the potential oral manifestations of diabetes mellitusand treatment considerations.Keywords: , , , , ,